2008
DOI: 10.1021/ic801101k
|View full text |Cite
|
Sign up to set email alerts
|

Copper β-Octakis(trifluoromethyl)corroles: New Paradigms for Ligand Substituent Effects in Transition Metal Complexes

Abstract: The reaction of copper beta-octabromo- meso-triarylcorrole derivatives with methyl 2,2-difluoro-2-(fluorosulfonyl)acetate has provided four beta-octakis(trifluoromethyl)corrole complexes, Cu[(CF 3) 8T( p-XP)C] (X = F, H, Me, OMe), in moderate yields. The new complexes present a conglomeration of remarkable substituent effects, both steric and electronic. DFT (OLYP/TZP) geometry optimization of Cu[(CF 3) 8TPC] (i.e., X = H) indicates a sterically hindered, strongly saddled geometry, with numerous short F...F no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 32 publications
2
76
0
Order By: Relevance
“…As noted before, [16] the CF 3 fluorine atoms appear as quartets with high 5 J FF coupling constants (≈10-15 Hz) in the 19 F NMR spectra at room temperature and above. This was interpreted as reflecting fast rotation (on the NMR timescale) of the congested, but dynamically geared CF 3 groups; thus, each CF 3 fluorine is only split by the three fluorines on the neighboring CF 3 group.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…As noted before, [16] the CF 3 fluorine atoms appear as quartets with high 5 J FF coupling constants (≈10-15 Hz) in the 19 F NMR spectra at room temperature and above. This was interpreted as reflecting fast rotation (on the NMR timescale) of the congested, but dynamically geared CF 3 groups; thus, each CF 3 fluorine is only split by the three fluorines on the neighboring CF 3 group.…”
Section: Resultssupporting
confidence: 68%
“…Thus, between X = H and X = OCH 3 , the Soret maximum of Cu[(CF 3 ) 8 T(p-X-P)C] is redshifted by 48 nm. [16] The corresponding shifts are only 20 nm and 29 nm for the Cu[T(p-X-P)C] and Cu[Br 8 T(p-X-P)C] series, [25] respectively. In our synthetic paper on the subject, [16] we suggested that the large meso shifts for the β-(CF 3 Kohn-Sham MO energy levels ( Figure 5) are in qualitative accord with differences in electrochemical redox potentials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20,23] Thus, copper triarylcorroles exhibit strongly meso-substituent-sensitive Soret maxima, [21,22] while goldt riarylcorroles do not.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent study was hampered by synthetic inaccessibility of corroles until 1999, when two new routes to the preparation of free base corrole were published by Paolesse 11 and Gross. 12,13 Over the next decade, a wealth of synthetic methodologies and variants were developed for synthesis of corroles, 14 with mesosubstituents, [15][16][17][18][19][20][21] various beta-substituents, [22][23][24][25][26] and eventually including both charged 27,28 and chiral 29 free-base corroles. The development of these organic syntheses is beyond the scope of this review, but the range of properties imparted by these synthetic options has greatly broadened the scope of applications of corroles.…”
Section: Introductionmentioning
confidence: 99%